Editors' Introduction: ECRA Vol. 6, No. 3 - Chau, Patrick Y. K. (Institutional Knowledge at Singapore Management University, 2007)
This issue features a total of 10 articles. The first eight articles are part of a special issue edited by Professors Karl L. Lang and Zhangxi Lin under the supervision of Professor Robert J. Kauffman. These articles are based on some of the best work originally presented at the Seventh International Conference on Electronic Commerce (ICEC 2005), held in August 2005 in Xian, China. The articles, which focus on different aspects of online negotiation and trade, were later extended and refined for presentation in ECRA. In addition, this issue also includes two regular submissions.Summaries of articles appearing in the special issue on “Online Negotiation and Trade” are provided in the guest editors’ introduction. The two regular submission articles complement those in the special issue by looking at issues of trust relationships in multi-party protocols and by presenting a novel revocation scheme for one-to-many e-services.Specifically, in “Exclusions and related trust relationships in multi-party fair exchange protocols”, Nicolás González-Deleito and Olivier Markowitch revisit multi-party fair exchange protocols, namely protocols that can be used to model a number of real-world electronic commerce transactions such as purchases made with credit cards (where parties include a customer, a merchant and their respective banks) or other electronic transactions involving more than two participants. The authors show that protocols proposed earlier in the literature can be subject to different types of attacks involving the exclusion of one or more participants. When such attacks take place, the protocols no longer offer the fairness guarantees that are critical to their acceptance or may lead excluded participants to assume that some parties are dishonest (“passive conspirators”) when they are not, thereby damaging their reputation. In contrast, the authors introduce two new multi-party fair exchange protocols intended to mitigate these problems.In “An innovative revocation scheme for one-to-many E-services”, Ren-Hung Lin and Jinn-Ke Jan look at the challenge of encrypting content in the context of one-to-many E-services such as a Pay-TV service whose customers are not necessarily online all the time. Customers of such services risk missing re-keying messages and may no longer be able to decrypt the service’s content. Instead the authors propose a new revocation scheme that reduces key storage requirements for service providers and does not require customers to continuously stay online. The proposed solution also allows users to simultaneously select from a number of e-services.We would like to take this opportunity to thank the special issue editors for the high quality of their work and for their diligence. Many thanks also to the reviewers for the detailed feedback they provided to the authors, and to the authors for their willingness to improve their papers for publication.